A research agenda for shrinking cities. - Hollander, Justin B. (Elgar, 2018)
This prescient book presents the intellectual terrain of shrinking cities while exploring the key research questions in each of the field s sub-domains and reviewing the range of methodologies within these topics. The book begins with an introduction outlining what shrinking cities are and how they are researched, highlighting both the opportunities and challenges that arise in this field, including the big ideas any researcher must grapple with. The next six chapters are each devoted to a different sub-domain within shrinking cities, offering a quick overview of the topics, relevant problems, paradoxes and key research questions. The author concludes with a review of the major themes and, most importantly, looks toward the future, predicting and anticipating the most significant future research trends related to shrinking cities. This accessible and compelling Research Agenda will be of interest to researchers looking to move into this area. It will also appeal to urban studies and planning instructors who are teaching research methods courses, and students studying or independently researching shrinking cities.
Keywords: Stadtforschung; Stadtentwicklung; Bevölkerungsentwicklung; Stadtsoziologie; Schrumpfung; Brachfläche; Nutzungsänderung; Feldforschung; Stadtkrise; Altindustrialisierte Region; Schrumpfende Stadt; Gebäudeleerstand